Implementasi EDM dan e-RKAM dalam Meningkatkan Mutu Pendidikan di MAN 2 Sragen Tahun 2021/2022 - Agung Febriawan; Syamsul Bakri (Neolectura, 2022)
This study aims to get an overview of the implementation and improvement of the quality of education through self-evaluation of madrasahs and electronic- work plans and budgets in MAN 2 Sragen. This research uses a qualitative method where all information obtained from observations and interviews is described in the form of written narratives as findings in the field. The implementation of EDM and e-RKAM is carried out by evaluating the madrasah itself through an internal quality audit by looking at and adjusting to the madrasah quality audit instrument system. The results of the study illustrate that the implementation of EDM and e-RKAM in MAN 2 Sragen has been implemented properly and organized. The preparation of e-RKAM is prioritized based on the results of recommendations from the EDM that have been implemented by the madrasah quality assurance team. There are obstacles in the implementation of implementation, namely (a) Limited human resources, (b) short time, (c) changing EDM systems and instruments. Supporting factors are (a) support from the Ministry of Religion of Sragen Regency and the Central Java region, (b) coordination between leaders, (c) communication and a sense of family between school residents. The benefits of EDM implementation are to find out the extent of the weaknesses and advantages of madrasah performance, the strengths of madrasahs and the quality of madrasahs that will be integrated for the preparation of e-RKAM to match the actual conditions.